PENGARUH PEMBIMBING AKADEMIK MELALUI KOMUNIKASI INTERPERSONAL DAN FASILITAS PEMBELAJARAN DALAM MEMOTIVASI MAHASISWA JURUSAN NON REKAYASA POLITEKNIK NEGERI SRIWIJAYA - Lisnini Lisnini; Esya Alhadi; Yusleli Herawati (Politeknik Negeri Sriwijaya, 2014)
The aim of this research is to know the influence of academic consultant through interpersonal communication and teaching learning facilities to student motivation of non engeneering department. The method used in this research was survey method.The population in this research is 1719 students and the number of samples were 95 students. The technique of data collection was using distribution questionnaires. To measure the influence among the variables used tools of quantitative analysis using spss version 12.0. The result showed that independence variables are interpersonal communication and teaching learning facilities simultaneously affected toward students learning motivation are 43.40 %. And the two independence and dependence variables the influence partial toward students learning motivation. Factor dominant in the influence toward student learning motivation is teaching learning facilities.